Nanostructured Ti-13Nb-13Zr alloy for implant application—material scientific, technological, and biological aspects - Klinge, Lina; Kluy, Lukas; Spiegel, Christopher; Siemers, Carsten; Groche, Peter; Coraça-Huber, Débora (Frontiers in Bioengineering and Biotechnology, 2023)
In dentistry, the most commonly used implant materials are CP-Titanium Grade 4 and Ti-6Al-4V ELI possessing a comparably high Young’s modulus (> 100 GPa). In the present study, the second-generation titanium alloy Ti-13Nb-13Zr is investigated with respect to the production of advanced dental implant systems. This should be achieved by the fabrication of long semi-finished bars with high strength and sufficient ductility to allow the automated production of small implants at a low Young’s modulus (< 80 GPa) to minimize stress shielding, bone resorption and gap formation between bone and implant. In addition, bacterial colonization is to be reduced and bone adhesion is to be enhanced by adjusting the microstructure. To do so, a dedicated thermo-mechanical treatment for Ti-13Nb-13Zr alloy has been developed. This includes the adaption of equal channel angular swaging, a modern process of severe plastic deformation to continuously manufacture nanostructured materials, to Ti-13Nb-13Zr and short-time recrystallization and ageing treatments. In particular, two-pass equal channel angular swaging at a deformation temperature of 150 °C and a counterpressure of 8 MPa has successfully been used to avoid shear band formation during deformation and to produce long Ti-13Nb-13Zr bars of 8 mm diameter. During a recrystallization treatment at 700 °C for 10 minutes followed by water quenching sub-micron-size primary α-phase in a matrix of α"-phase developed. Subsequent ageing at 500 °C for one hour lead to martensite decomposition and, thus, to a homogeneously nanostructured microstructure of α- and β-phase with substructures smaller than 200 nm. The resulting mechanical properties, especially the ultimate tensile strength of more than 990 MPa, fulfill the requirements of ASTM F1713 at a Young’s modulus of 73 GPa. Biological investigations show promising results in reducing bacterial biofilm formation and increased cell proliferation of osteoblasts compared to CP-Titanium Grade 4 and Ti-6Al-4V ELI, especially, if etched surfaces are applied.